Juridical Analysis of the Judgment of Acquittal from All Lawsuits for Perpetrators of Defamation Through Social Media - Maskur, Apriyanti (Candela Edutech Indonesia, 2025)
This study aims to examine the suitability of the Judge's considerations in Decision Number 98/Pid.Sus/2020/PN Sos with the trial facts and the implications of Decision Number 98/Pid.Sus/2020/PN Sos. The type of research used is normative legal research which is a research method that focuses on positive legal norms. The data collected in this study include secondary data sources from legal literature with data collection techniques in the form of literature studies of legal materials and then analyzed qualitatively using descriptive methods. The results of the study on Decision Number 98/Pid.Sus/2020/PN Sos can be explained that the Panel of Judges' considerations are basically inappropriate, because Article 49 paragraph (1) of the Criminal Code only covers honor in the sense of the sexual field so that it cannot be used to argue for a defense of honor in the sense of a good name, besides that, the defendant's actions do not fulfill the element of